2016
DOI: 10.1111/mpp.12409
|View full text |Cite
|
Sign up to set email alerts
|

An effector of apple proliferation phytoplasma targets TCP transcription factors—a generalized virulence strategy of phytoplasma?

Abstract: The plant pathogen Candidatus Phytoplasma mali (P. mali) is the causative agent of apple proliferation, a disease of increasing importance in apple-growing areas within Europe. Despite its economic importance, little is known about the molecular mechanisms of disease manifestation within apple trees. In this study, we identified two TCP (TEOSINTE BRANCHED/CYCLOIDEA/PROLIFERATING CELL FACTOR) transcription factors of Malus x domestica as binding partners of the P. mali SAP11-like effector ATP_00189. Phytohormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 53 publications
4
77
0
Order By: Relevance
“…Additionally, jasmonic acid levels in infected Arabidopsis leaves are significantly reduced in comparison with untreated leaves, indicating that the plant’s defense mechanisms are reduced upon infection by the pathogen. A similar effect has been found in apples, where the plant pathogen Candidatus Phytoplasma mali binds to two TCP transcription factors and induces morphogenetic changes that co-occur with reduction of jasmonic acid, salicylic acid, and abscisic acid levels (Janik et al, 2016). Further studies identified the class I TCPs TCP8 and TCP9 as important factors for the expression of ICS1 , which encodes for a key enzyme in salicylic acid synthesis (Wang X.et al, 2015).…”
Section: Mediating Environmental Signals Into Growth Responsessupporting
confidence: 55%
“…Additionally, jasmonic acid levels in infected Arabidopsis leaves are significantly reduced in comparison with untreated leaves, indicating that the plant’s defense mechanisms are reduced upon infection by the pathogen. A similar effect has been found in apples, where the plant pathogen Candidatus Phytoplasma mali binds to two TCP transcription factors and induces morphogenetic changes that co-occur with reduction of jasmonic acid, salicylic acid, and abscisic acid levels (Janik et al, 2016). Further studies identified the class I TCPs TCP8 and TCP9 as important factors for the expression of ICS1 , which encodes for a key enzyme in salicylic acid synthesis (Wang X.et al, 2015).…”
Section: Mediating Environmental Signals Into Growth Responsessupporting
confidence: 55%
“…Other groups also identified many TCPs as interactors in their Y2H screens with unrelated baits, suggesting that these TCPs readily interact in the Y2H. For example, TCP8, TCP14, and TCP15 were found to interact with various effector proteins of unrelated plant pathogens (Sugio et al, 2011 , 2014 ; Weßling et al, 2014 ; Janik et al, 2017 ; Yang et al, 2017 ), but these TCPs also interacted with SUPPRESSOR OF rps4-RLD1 (SRFR1), a negative regulator of effector-triggered immunity (Kim et al, 2014 ). In this latter case, these interactions were only found with one class of TCPs suggesting that they were bona fide interactions.…”
Section: Resultsmentioning
confidence: 99%
“…In witches' broom, the phytoplasma effector SAP11 causes the degradation of A. thaliana TCP transcription factors that repress branching and mediate leaf development; this results in branchy plants with crinkly leaves (Sugio et al, 2014). Homologs of these TCP transcription factors and SAP11 also interact in apple and in maize, where phytoplasmas cause witches' broom and disrupted floral development, respectively (Janik et al, 2017;Pecher et al, 2019). Thus, protein-protein interactions between conserved host transcription factors and pathogen effectors can link developmental regulation and proteasome degradation, resulting in large-scale changes to plant form.…”
Section: Phytoplasma Effectors and Developmental Remodelingmentioning
confidence: 99%